FROM LEAN MANAGEMENT IN HEALTHCARE TO LEAN HEALTHCARE - Поплавська, Жанна; Годиш, Ярослав (SWorldJournal, 2025)
The paper examines the possibilities of using the principles of Lean healthcare as an approach based on lean management - a management concept aimed at maximizing benefits for clients while minimizing the waste of human and material resources. Lean Health